2016
DOI: 10.21608/jssae.2016.39766
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Locally Vacuum Vegetable Seeder for Nursery Trays

Abstract: A continuous feeding mechanism for precision vacuum trays seeder was developed and fabricated from locally materials for seeding single seed in the trays. The developed seeder was evaluated under two trays types of 84 and 209 cells, four different suction pressure levels (0.5, 1, 1.5 and 2 kPa) & (0.3, 0.6, 0.9 and 1.2 kPa) and four different hole size diameters of seed plate (1.2, 1.4, 1.6, 1.8 mm) & (0.4, 0.6, 0.8, 1.0 mm) for cucumber and cabbage seeds respectively. The seeding unit comprises of different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…There are several types of these trays, some of which are made of flexible plastic material, and some of which are made of compressed cork, which is a good thermal insulator to protect the seed in the early stages of its life, and both types are available in different sizes [2]. The total power requirements IOP Publishing doi:10.1088/1755-1315/1262/9/092008 2 (kw) of the model designed by [3] included calculating the power of the electric motor of the seeding machine as well as the power of the air suction pump. Focus [4] on choosing the optimal power for the motors that rotate the conveyor belts, so that they bear the weight and the design does not fail when running.…”
Section: Introductionmentioning
confidence: 99%
“…There are several types of these trays, some of which are made of flexible plastic material, and some of which are made of compressed cork, which is a good thermal insulator to protect the seed in the early stages of its life, and both types are available in different sizes [2]. The total power requirements IOP Publishing doi:10.1088/1755-1315/1262/9/092008 2 (kw) of the model designed by [3] included calculating the power of the electric motor of the seeding machine as well as the power of the air suction pump. Focus [4] on choosing the optimal power for the motors that rotate the conveyor belts, so that they bear the weight and the design does not fail when running.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that their seeder achieved a single-seeding rate of more than 90% at approximately 15.27% of the overall cost of manual seeding. EL-Ghobashy et al [2] proposed a continuous feeding mechanism for precision plug tray seeders and compared two plug tray types, four suction pressure levels, and four suction hole diameters for cucumber and cabbage seeding; they reported that their precision plug tray seeder resulted in 5-12-fold cost reductions compared with manual seeding. Plug trays with 104 cells are commonly used to promote the germination of many vegetable and fruit seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…China ranks first in vegetable production and consumption in the world, and is the world's largest vegetable exporter (Qi et al, 2020). However, there is still a big gap in the level of comprehensive mechanization compared with developed countries (Li et al,2019 ;Richard, 2005;Xiao et al, 2017), especially in facilities greenhouses vegetables sowing, the space is narrow, the working distance is short and the manual dependence is strong (Narang et al, 2012;EL-Ghobashy et al, 2016;Du et al, 2017;Jin et al, 2019), with the shortage of rural labor force, the problem of expensive labor and difficult labor in vegetable production is becoming more and more prominent. Therefore, it is of great significance to study efficient intelligent equipment to improve the production efficiency of facilities greenhouses vegetables, reduce manual dependence and improve the mechanization level of vegetable production.…”
Section: Introductionmentioning
confidence: 99%